Prednisolone-Induced Hairy Tongue: A Case Report - Sevcan UĞUR,; Cahit KAÇAR, (Archives of Rheumatology, 2019)
Hairy tongue is a benign and mostly asymptomatic disorder characterized by elongation of papillae with typical hairy-like appearance on the dorsal surface of the tongue. Many medical conditions, antibiotics, and drugs inducing xerostomia are associated with hairy tongue. In this article, we report a female patient with polymyalgia rheumatica who developed hairy tongue following treatment with prednisolone. Clinicians should be aware of the predisposing factors and drugs that may have a role in the development of hairy tongue.